PROBLEMATIKA HUKUM PUTUSAN RECHTERLIJK PARDON DALAM SISTEM PEMIDANAAN DI INDONESIA - Lase, Jovial Kristian; R, Mukhlis; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The background of the concept of rechterlijk pardon is rooted in theprevalence of defendants who have actually fulfilled the burden of proof, butsentencing them would result in a conflict between legal certainty and justice. Onthe other hand, the qualification procedure for rechterlijk pardon must be strictlyregulated to ensure that pardons are not granted without guidelines, given thewide discretion available to judges. Rechterlijk pardon in the penal systemprimarily concerns the imposition of penalties where judges may decide not toimpose a sentence on proven guilty defendants based on the goals of sentencing.The analysis employs normative research using a qualitative approach,specifically conceptual and legislative approaches, to uncover how judges weighdecisions and the constraints that govern judges in rechterlijk pardon rulings.The findings of this research suggest that legal reasoning by judges mustalign with moral reasons consistent with Pancasila values and civilized law, andshould focus on individualizing punishment and subsociality in formulatingsentencing goals. Sentencing guidelines are intended as a controlling function.The highly individual characteristics of criminal cases should be autonomouslyjustified with sufficient consideration of legal principles and the principle of culpain causa.Keywords: Rechterlijk Pardon, Verdict, Penal System